Factor Determinant Implementation Vaccines for the Elderly - Elzina Dina De Fretes; Tri Juniarti (Institute of Computer Science (IOCS), 2022)
The elderly are vulnerable and at-risk groups exposed to the Covid 19 virus. However, the number of achievements immunization in the elderly is still relatively low compared to group age other. Various factors cause this thing. Destination study this to know the factors that influence implementation vaccine in advanced age. This research is an analytical research observation with an approach to a cross-sectional study. This research was carried out in the working area of Fakfak City Health Centre within six months for the elderly aged more than 60 years old as many as 30 selected respondents used consecutive sampling techniques. This study used a questionnaire instrument. Data analysis used linear logistic regression analysis. The study find that the distance factor to facility health, level of obtained information, and knowledge is a factor that influences the reception of vaccine in advanced age with a p-value <0.05. we recommend that the elderly, with all the limitations in access to the Covid-19 vaccine, can be facilitated by the government, including access to facility provider vaccination and access information. Future research could focus on the proper intervention on the problem enhancement knowledge, access information nor intervention for seniors who want to get vaccine however blocked by access distance to location vaccination.